Prácticas artísticas contemporáneas en las enseñanzas oficiales obligatorias. Experiencias de arte de acción en la educación secundaria obligatoria - Cueto, Belén (2019)
From the beginning of my teaching I wonder how to introduce, in a structure as regulated as compulsory secondary education, contemporary artistic practices and specifically action /performance. It was proposed to do an individual action, another in pairs or trios, and another collective action with the whole group. The starting question: Am I part of nature?